(untitled) (American Journal of Technology and Applied Sciences, 2023)
The purpose of this work is to study the effect of the operational properties of oils on the technical condition of the engine. The performance properties of oils are understood as a set of those physico-chemical and functional properties that determine the effect of oils on the main performance indicators of the car. The estimated coefficient of quality of lubricants is determined.